Diseño de un prototipo a bajo costo para la cuantificación de hidrógeno (2025)
This project proposes the design and development of a portable, low-cost prototype for hydrogen quantification, aimed at academic and research applications. The need for accessible tools for gas measurement arises because conventional methods, such as gas chromatography, require specialized equipment. Also, commercially available devices, such as the GasAlert Micro 5 PID and the RKI GX-6000, are expensive. The prototype was based on the use of the MQ-8 sensor, which operates by varying its electrical resistance when detecting hydrogen. To improve its performance, a 3D printed capsule was integrated, allowing the interaction of the gas with the sensor to be optimized and its measurement range to be extended. In addition, an Arduino board was used for data acquisition and processing.